(3aYdJ adG Jde aj GdgjFIs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s ((3eMeO Hf YHO Gddg GdeOYh HCHi GddjK GdSJGQGf s)
(3ChdgG (B:s
(3CeG HYO MeOkG ddg NGdb GdCadGc heOjQgG hbO hbY Edi cJGH ef fhGHY GdedhGf SeGg JHjGf ebGUO GdJPcQI s
(3BNQgG (B:s
(3hYfO Gddg JYGdi GMJSH eOI VjYJgG h JUaM CbGhjdc hCf jLYdfi HSYGOI GdCHO ef GdaGFRjf hdYbGHg ef GdCefjf s
(3YdjgG Jedcs
(3fbdJ Yf fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
Keywords: (3Gdadcs